Real-time 2D Concentration Measurement of CH4 in Oscillating Flames Using CT Tunable Diode Laser Absorption Spectroscopy - Kamimoto, Takahiro; Deguchi, Yoshihiro; Zhang, Ning; Nakao, Ryosuke; Takagi, Taku; Zhang, Jia-Zhong (Journal of Applied Nonlinear Dynamics, 2026)
Foreign Object Debris (FOD) is debris or article alien, which may One of the major problems of gas turbine combustors is the combustion oscillation. The combustion oscillation of gas turbines has many complex causes such as pressure fluctuations, combustion instabilities, and mechanical designs of the combustion chamber. Although the significant research efforts have been dedicated to this topic, the combustion oscillation problems have not yet been solved because of its complexity and nonlinearity. In this study, the theoretical and experimental research has been conducted in order to develop the noncontact and fast response 2D CH4 distribution measurement method to elucidate nonlinear combustion oscillation problems. The method is based on a computed tomography (CT) method using tunable diode laser absorption spectroscopy (TDLAS). The CT-TDLAS method was applied to oscillating flames and the time resolved 2D CH4 concentration distributions were successfully measured using 16 path CT-TDLAS measurement cell. CT-TDLAS has the kHz response time and the method enables the real-time 2D species concentration measurement to be applicable to the nonlinear phenomena of combustion oscillation problems in gas turbines.